Lifelong learning as integrational resource of knowledge economy - Tkach, Anatoliy (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper examines the meaning and the main features of the knowledge economy. It also analyses present-day challenges for the knowledge economy under new economic conditions. Research indicates arguments justifying the thesis that knowledge is a specific resource, which, unlike all other economic resources, can be unlimited under the condition of the continuous nature of education. Modern problems of market economy require deep rethinking and effective use of the characteristics of the knowledge economy for building new market relationships. Current economic problems will be successfully solved if one carefully considers the features of the Knowledge economy. The expanding Internet, ever more powerful mobile devices, and other innovations make the task of designing effective formal and informal learning challenging, especially in light of the high rate of change in these new technologies.

Artykuł poddaje pod dyskusję znaczenie i główne cechy gospodarki opartej na wiedzy. Analizuje również współczesne wyzwania dla gospodarki opartej na wiedzy w nowych warunkach gospodarczych. Badania wskazują argumenty uzasadniające tezę, że wiedza jest specyficznym zasobem, który, w przeciwieństwie do wszystkich innych zasobów gospodarczych, może być nieograniczony pod warunkiem ciągłego charakteru edukacji. Współczesne problemy gospodarki rynkowej wymagają głębokiego przemyślenia i efektywnego wykorzystania cech gospodarki opartej na wiedzy w tworzeniu i kształtowaniu nowych relacji rynkowych. Aktualne problemy gospodarki zostaną pomyślnie rozwiązane, jeśli weźmie się pod uwagę cechy gospodarki opartej na wiedzy. Rozwijający się Internet i inne innowacje sprawiają, że zadanie projektowania skutecznego uczenia się formalnego i nieformalnego staje się wyzwaniem, szczególnie w świetle wysokiej dynamiki zmian w sferze nowych technologii.
Keywords: lifelong learning; innovations; education; knowledge-based economy; human capital; innovative economy; uczenie się przez całe życie; innowacje; edukacja; gospodarka oparta na wiedzy; kapitał ludzki; innowacyjna gospodarka